2018
DOI: 10.1111/jce.13493
|View full text |Cite
|
Sign up to set email alerts
|

An electrocardiographic diagnostic model for differentiating left from right ventricular outflow tract tachycardia origin

Abstract: A highly accurate ECG diagnostic model for correctly differentiating LVOT origin from right ventricular outflow tract origin was developed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 20 publications
0
29
0
Order By: Relevance
“…We used DeLong's test (DeLong et al, 1988) to demonstrate that the automated ECG feature extraction method had a significantly higher AUC compared with that attained by the conventional QRS morphological feature extraction approach with a P-value = 0.035. The comparison of our approach against methods from 12 prior studies (Kamakura et al, 1998;Zhang et al, 2009;Betensky et al, 2011;Yoshida et al, 2011Yoshida et al, , 2014Cheng et al, 2013Cheng et al, , 2018Nakano et al, 2014;Efimova et al, 2015;He et al, 2018;Xie et al, 2018;Di et al, 2019) shows that our algorithm achieved the highest performance scores (shown in Table 3). Additionally, we evaluated the general classification capability of each criterion proposed by previous studies using the database in this study.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…We used DeLong's test (DeLong et al, 1988) to demonstrate that the automated ECG feature extraction method had a significantly higher AUC compared with that attained by the conventional QRS morphological feature extraction approach with a P-value = 0.035. The comparison of our approach against methods from 12 prior studies (Kamakura et al, 1998;Zhang et al, 2009;Betensky et al, 2011;Yoshida et al, 2011Yoshida et al, , 2014Cheng et al, 2013Cheng et al, , 2018Nakano et al, 2014;Efimova et al, 2015;He et al, 2018;Xie et al, 2018;Di et al, 2019) shows that our algorithm achieved the highest performance scores (shown in Table 3). Additionally, we evaluated the general classification capability of each criterion proposed by previous studies using the database in this study.…”
Section: Discussionmentioning
confidence: 79%
“…The classification confusion matrix for these three methods shows correct and incorrect frequency counts in Supplementary Section A and Table 3. Furthermore, we compared our approach against related methods from 12 prior studies (Kamakura et al, 1998;Zhang et al, 2009;Betensky et al, 2011;Yoshida et al, 2011Yoshida et al, , 2014Cheng et al, 2013Cheng et al, , 2018Nakano et al, 2014;Efimova et al, 2015;He et al, 2018;Xie et al, 2018;Di et al, 2019). ACC, F 1 -score, SE, SP, positive predictive value, negative predictive value, and AUC were used to compare performances and are shown in Table 3.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The stepwise algorithm is beneficial for improving the accuracy of predicting the LVOT origin, which makes contributions to guiding to choose the right access, reducing the scope of intracardiac mapping, saving the mapping time, and improving the success rate of ablation. To distinguish LVOT from RVOT origin accurately, He et al [26] used similar ECG algorithms to develop an ECG diagnostic equation: Y = -1.15 × (TZ) -0.494 × (V2S/V3R). However, its usage and promotion would be restricted because of the complex calculation.…”
Section: Discussionmentioning
confidence: 99%
“…An accurate prediction of RVOT and LVOT origins of OTVT can optimize the CA strategy, reduce ablation duration, and avoid operative complications. Previous studies 3,[6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] have proposed several criteria or models to estimate RVOT and LVOT origins. However, these results have been limited by sample size, the scope of studies, ECG measurement efficiency, and the generalizability of the models.…”
Section: Introductionmentioning
confidence: 99%